(untitled) (Altre Modernità, 2014)
Among the spaces inhabited and crossed by spies and spy stories, that of the museum is certainly one of the most intriguing. This essay analyses different spy figures who, for very different reasons and in very different contexts (both real and fictitious), have related with museums: Sir Anthony Blunt, the connoisseurs working in disguise for KGB in Alan Bennett’s play A Question of Attribution (1988), and the Russian secret agents working in an operation’s room hidden in the basement of the Hermitage museum in St. Petersburg in the spy story Op-Center. Mirror Image (1981) by Tom Clancy and Steve Pieczenik, written by Jeff Rovin. There are many reasons for this fortunate marriage between museums and espionage. First of all, the fact that museums prioritize the visual experience make them a very pregnant metaphor for espionage activity, based on observation and control and on tools such as binoculars, magnifying glasses and miniature cameras. Secondly, like the world of espionage, museums are places of danger and ambush, where nothing is what it seems and where it is difficult to make out real from fake. Furthermore, the methods of investigations of the spy are very similar to the art of connoisseurship of the art historian.